Robusta Coffe-Derived Silver Nanoparticles as a Natural Photosensitizer for Photodynamic Inactivation of Bacterial Biofilms - Amruloh, Yazid Muhammad; Astuti, Suryani Dyah; Arifianto, Deny; Nurdin, Dezy Zahrotul Istiqomah; Zaidan, Andi Hamim; Widiyanti, Prihartini; Yaqubi, Ahmad Khalil; Winarno; Abd Razak, Nasrul Anuar (Institute of Topical Disease Universitas Airlangga, 2025)
Bacterial biofilm formation represents a major challenge in clinical settings, as it contributes to persistent infections and resistance to conventional antimicrobial treatments. This study investigates the effectiveness of blue laser therapy combined with AgNPs-CR in inhibiting biofilm formation by Escherichia coli and Staphylococcus aureus, common infection agents, in a four-group sample set. Silver nanoparticles, known for their antibacterial, antifungal, and antiviral properties, are widely used in biomedical devices. First, the control group (T0) included samples without laser irradiation. Second, the Escherichia coli and Staphylococcus aureus groups (A1 and A2) were irradiated with a 405 nm diode laser at various exposure times and silver nanoparticle concentrations. Third, the E. coli and S. aureus groups (A3 and A4) were also irradiated with the 405 nm diode laser under varying durations and concentrations of silver nanoparticles. In groups A2 and A4, the bacteria were treated with the photosensitizer AgNPs-CR, incubated for 30 minutes, and then irradiated for 90, 120, 150, and 180 seconds. The results were analyzed using a two-way factorial ANOVA and a Post-hoc Tukey test, with a significance level of p < 0.05. Photodynamic therapy (PDT) significantly inhibited bacterial biofilms in samples with irradiation, with the most significant reduction observed at a concentration of 2 mM and 180 seconds of irradiation, compared to samples without irradiation. Staphylococcus aureus was the most susceptible to AgNPs, showing a high biofilm inhibition percentage of 94.82% at 180 seconds of irradiation with a 2 mM concentration. Fluorescence microscope analysis revealed the presence of bacterial DNA corresponding to 180 colonies.